Fabrication of ZnO and TiO2 Nanotubes via Flexible Electro-Spun Nanofibers for Photocatalytic Applications - Monica Enculescu; Andreea Costas; Alexandru Evanghelidis; Ionut Enculescu (Nanomaterials, 2021)
Web-like architectures of ZnO and TiO2 nanotubes were fabricated based on a three-step process of templating polymer nanofibers produced by electrospinning (step 1). The electrospun polymer nanofibers were covered by radio-frequency magnetron sputtering with thin layers of semiconducting materials (step 2), with FESEM observations proving uniform deposits over their entire surface. ZnO or TiO2 nanotubes were obtained by subsequent calcination (step 3). XRD measurements proved that the nanotubes were of a single crystalline phase (wurtzite for ZnO and anatase for TiO2) and that no other crystalline phases appeared. No other elements were present in the composition of the nanotubes, confirmed by EDX measurements. Reflectance spectra and Tauc plots of Kubelka–Munk functions revealed that the band gaps of the nanotubes were lower than those of the bulk materials (3.05 eV for ZnO and 3.16 eV for TiO2). Photocatalytic performances for the degradation of Rhodamine B showed a large degradation efficiency, even for small quantities of nanotubes (0.5 mg/10 mL dye solution): ~55% for ZnO, and ~95% for TiO2.